Dodecyl-TPP Targets Mitochondria and Potently Eradicates Cancer Stem Cells (CSCs): Synergy With FDA-Approved Drugs and Natural Compounds (Vitamin C and Berberine) - De Francesco, Ernestina Marianna; Ózsvári, Béla; Sotgia, Federica; Lisanti, Michael P. (Frontiers in Oncology, 2019)
Elevated mitochondrial biogenesis and/or metabolism are distinguishing features of cancer cells, as well as Cancer Stem Cells (CSCs), which are involved in tumor initiation, metastatic dissemination, and therapy resistance. In fact, mitochondria-impairing agents can be used to hamper CSCs maintenance and propagation, toward better control of neoplastic disease. Tri-Phenyl-Phosphonium (TPP)-based mitochondrially-targeted compounds are small non-toxic and biologically active molecules that are delivered to and accumulated within the mitochondria of living cells. Therefore, TPP-derivatives may represent potentially “powerful” candidates to block CSCs. Here, we evaluate the metabolic and biological effects induced by the TPP-derivative, termed Dodecyl-TPP (d-TPP) on breast cancer cells. By employing the 3D mammosphere assay in MCF-7 cells, we demonstrate that treatment with d-TPP dose-dependently inhibits the propagation of breast CSCs in suspension. Also, d-TPP targets adherent “bulk” cancer cells, by decreasing MCF-7 cell viability. The analysis of metabolic flux using Seahorse Xfe96 revealed that d-TPP potently inhibits the mitochondrial oxygen consumption rate (OCR), while simultaneously shifting cell metabolism toward glycolysis. Thereafter, we exploited this ATP depletion phenotype and strict metabolic dependency on glycolysis to eradicate the residual glycolytic CSC population, by using additional metabolic stressors. More specifically, we applied a combination strategy based on treatment with d-TPP, in the presence of a selected panel of natural and synthetic compounds, some of which are FDA-approved, that are known to behave as glycolysis (Vitamin C, 2-Deoxy-Glucose) and OXPHOS (Doxycyline, Niclosamide, Berberine) inhibitors. This two-hit scheme effectively decreased CSC propagation, at concentrations of d-TPP toxic only for cancer cells, but not for normal cells, as evidenced using normal human fibroblasts (hTERT-BJ1) as a reference point. Taken together, d-TPP halts CSCs propagation and targets “bulk” cancer cells, without eliciting the relevant undesirable off-target effects in normal cells. These observations pave the way for further exploring the potential of TPP-based derivatives in cancer therapy. Moreover, TPP-based compounds should be investigated for their potential to discriminate between “normal” and “malignant” mitochondria, suggesting that distinct biochemical, and metabolic changes in these organelles could precede specific normal or pathological phenotypes. Lastly, our data validate the manipulation of the energetic machinery as useful tool to eradicate CSCs.